(untitled) (Research, Society and Development, 2021)
This study aimed to describe the process of building and validating an instrument through Multivariate Analysis, in which the Factor Analysis technique combined with Cluster Analysis was used, in order to analyze the conceptions of high school students about the importance of the Science discipline in the ninth year of Elementary School, with an emphasis on Physics concepts (Optics). To this end, a pilot questionnaire was applied, made available virtually to 21 high school students from a federal public college, located in the city of Campo Grande in the state of Mato Grosso do Sul. This research is of a quantitative nature, in which it seeks to answer the object of study, being characterized as conclusive. The research requires defined, formal and structured information, so a sample is presented and the data analysis is statistical and conclusive. When applying all tests and analyzes (Cronbach’s Alpha, Bartlett’s Test, KMO, Principal Component Analysis, Factor Analysis and Cluster Analysis), it is concluded that the instrument has reliability, commonality, suitability and interdependence between the variables, being validated by Multivariate Analysis techniques.